MiR-124 Suppresses Growth of Human Colorectal Cancer by Inhibiting STAT3 - Zhang, Jufeng (Public Library of Science, 2013)
Emerging evidence indicate that microRNAs (miRNAs) may play important roles in cancer. Aberrant expression of miRNAs has been frequently identified in different human malignancies, including colorectal cancer (CRC). However, the mechanism by which deregulated miRNAs impact the development of CRC remains largely elusive. In this study, we show that miR-124 is significantly down-regulated in CRC compared to adjacent non-tumor colorectal tissues. MiR-124 suppresses the expression of STAT3 by directly binding to its 3′-untranslated region (3′-UTR). Overexpression of miR-124 led to increased apoptosis of CRC cells and reduced tumor growth in vitro and in vivo. Knocking down STAT3 expression by specific siRNA suppressed the growth of CRC cells in vitro and in vivo, resembling that of miR-124 overexpression. Moreover, overexpression of STAT3 in miR-124-transfected CRC cells effectively rescued the inhibition of cell proliferation caused by miR-124. These data suggest that miR-124 serves as a tumor suppressor by targeting STAT3, and call for the use of miR-124 as a potential therapeutic tool for CRC, where STAT3 is often hyper-activated.